1956
DOI: 10.1084/jem.103.2.247
|View full text |Cite
|
Sign up to set email alerts
|

An Endemiological Study of Enteric Virus Infections

Abstract: An endemiological study of enteric viruses was conducted among 136 normal children, living in households in two socio-economic groups, over a 29 month period in Charleston, West Virginia. A repeatable seasonal incidence of enteric virus excretion was noted with over 90 per cent of isolations occurring in the months of June to October. Of 592 stools examined in District I, a lower socio-economic group, 8.3 per cent yielded virus as compared to 3.1 per cent of 966 stools examined in District IV, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1956
1956
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The paucity of enteroviruses in the Seattle cohort and their comparative abundance in children from The Gambia is consistent with the model that these viruses are associated with children living in impoverished conditions. Culture-based studies from several decades ago of healthy children also demonstrated a greater frequency of excretion of enteroviruses among persons of lower socioeconomic status ( Honig et al, 1956 , Otatume and Addy, 1975 ). Additionally, a recent study in Seattle showed no enterovirus detection in stools from children with diarrhea ( Braun et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The paucity of enteroviruses in the Seattle cohort and their comparative abundance in children from The Gambia is consistent with the model that these viruses are associated with children living in impoverished conditions. Culture-based studies from several decades ago of healthy children also demonstrated a greater frequency of excretion of enteroviruses among persons of lower socioeconomic status ( Honig et al, 1956 , Otatume and Addy, 1975 ). Additionally, a recent study in Seattle showed no enterovirus detection in stools from children with diarrhea ( Braun et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…Figure 3 demonstrates that both of these waterborne diseases have the same seasonal pattern, so are highly appropriate comparison diseases. The seasonality in figure 3 coheres with contemporary detailed virological surveillance (Honig et al, 1956). Where typhoid and polio differ is that reinfection can occur with typhoid fever (Parry et al, 2002), whereas polio infection confers lifelong immunity.…”
Section: Datamentioning
confidence: 60%